J.P. Beaumont : Nothing to Lose - Book 28 - Jance, Judith A. (New York : William Morrow, an imprint of HarperCollins Publishers, 2022)
"Years ago, when J.P. Beaumont was a homicide detective with the Seattle PD, his partner, Sue Danielson, was murdered. Volatile and angry, Danielsons ex-husband came after her in her home and, with nowhere else to turn, Jared, Sues teenage son, frantically called Beau for help. As Beau rushed to the scene, he urged Jared to grab his younger brother and flee the house. In the end, Beaumonts plea and Jareds quick action saved the two boys from their fathers murderous rage. Now, almost twenty years later, Jared reappears in Beaus life seeking his help once again--his younger brother, Chris, is missing. Still haunted by the events of that tragic night, Beau doesnt hesitate to take on the case. Following a lead all the way to the wilds of wintertime Alaska, he encounters a tangled web of family secrets in which a killer with nothing to lose is waiting to take another life."--Back cover.
Keywords: Beaumont, J. P. (Fictitious character) -- Fiction; Police -- Washington (State); Seattle; Fiction; Private investigators -- Fiction; Missing persons -- Investigation; Fiction; Murder -- Investigation; Fiction; Family secrets -- Fiction; Seattle (Wash.) -- Fiction; Alaska -- Fiction; Detective and mystery fiction; Thrillers (Fiction)